The Influence Of Product Innovation, Promotion And Price Perception On The Decision To Purchase Healthy Dessert Cake Products In Sidoarjo District - Farah Nabilah; Endah Budiarti , (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This study aims to test whether the variables of product innovation, promotion, and price perception affect the purchase decision of kuey healthy dessert products in Sidoarjo Regency with a sample size of 97 respondents. The data collection method used is by distributing questionnaires. The analysis technique needed in this study is multiple linear regression, for hypothesis testing using the T Test, F Test, and Coefficient of Determination(R2), then the classical assumption test consists of Normality Test, Multicolinerity Test, and Heteroscedasticity Test, besides that there is an instrument test is Validity Test and Reability Test. The results showed that the F test simultaneously all independent variables together had an effect on the dependent variable, namely the purchase decision. While for the results of the T test research or partial product innovation variables have a significant and positive effect on purchasing decisions, promotional variables have a significant and positive effect on purchasing decisions and price perception variables have a significant and positive effect on purchasing decisions.